Preparation of Bioactive De-Chlorophyll Rhein-Rich Senna alata Extract - Wah Wah Aung; Kanokpon Panich; Suchawalee Watthanophas; Sutada Naridsirikul; Juthaporn Ponphaiboon; Wantanwa Krongrawa; Pattranit Kulpicheswanich; Sontaya Limmatvapirat; Chutima Limmatvapirat (MDPI AG, 2023)
Senna alata leaves display various biological activities as a result of their rhein and phenolic composition. The objective of this study was to develop bioactive de-chlorophyll rhein-rich S. alata extracts. The rhein content was quantified using a validated high-performance liquid chromatography-diode array detection (HPLC-DAD) method. The best process parameters for maximizing rhein were established using ultrasound-assisted extraction (UAE). The optimal conditions for the parameters were determined using the Box-Behnken design (BBD); 95% v/v ethanol was used as the extraction solvent at 59.52 °C for 18.4 min with a solvent-to-solid ratio of 25.48:1 (mL/g) to obtain the predicted value of rhein at 10.44 mg/g extract. However, the color of the rhein-rich extract remained dark brown. For the removal of chlorophyll, liquid-liquid extraction with vegetable oils and adsorption with bleaching agents were employed. The bleaching agents were significantly more effective at removing chlorophyll and had less of an effect on the reduction in rhein content than vegetable oils. The presence of rhein and phenolics in the de-chlorophyll extracts might be responsible for their antioxidant, anti-inflammatory, and antibacterial activities. These findings indicate that rhein-rich extract and its de-chlorophyll extracts possess sufficient biological activities for the further development of cosmeceuticals and pharmaceuticals.